PERBAIKAN SISTEM PENDINGIN (CONDENSOR) ALAT PENYULINGAN MINYAK NILAM UNTUK MENINGKATKAN RENDEMEN - jauhari, gamindra (LLDIKTI Wilayah X, 2014)
ABSTRACTRepairs to the cooling system (condenser) patchouli oil refinery in the oil refining Bandarejo pack Akmal in West Pasaman, managed to increase the average yield from 1.8 to 2.0% to 2.5625 to 2.8725% and the oil quality better comply with SNI 06-2385-2006. Further research is focused on the replacement of the heating system boiler water (steam) or boiler, which was previously made of the usual drum and kettle or boiler replaced with stainless steel juice. Initially, the researchers predicted an increase in yield of up to 3.3%, can be obtained after the replacement boiler or boiler with SS and in fact the increase of 5.57%, from an average yield of 2.875% to 3.035%. Results showed that the difference in the level of improvement drought raw materials affect yield and yield. 80% dryness level results and the yield is greater than the rate of drying of raw materials 95%. For every 40 kg of dry raw materials 80%, average yield of 1,214 kg with a production yield of 3.035%. Compared with every 40 kg of dry raw materials 95%, an average of 1.06 kg of their products with a yield of 2.65%.Keywords: patchouli oil, yield, quality, kettle